(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study presents a comparative linguistic analysis of the onomastic systems in Uzbek and English. The research focuses on the classification, formation, and cultural semantics of proper names, particularly anthroponyms and toponyms. By employing a descriptive and comparative methodology, the paper identifies both universal patterns and language-specific features in name formation. The findings reveal that while both languages reflect deep cultural and historical roots in their onomastics, Uzbek names are more influenced by social hierarchy and Islamic traditions, whereas English names display greater diversity influenced by historical invasions and colonization. The study contributes to cross-linguistic onomastics and highlights the significance of names in sociolinguistic identity.